Perlindungan Hukum Bagi Korban Amuk Massa - Liza Deshaini (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2021)
Mass rage is a form of aspiration that is not conveyed properly. The great upheaval arose because of the aspirations that had been the pent up does not have a container to channel it properly so that a great upheaval occurs. Mass tantrums can also arise because of personal disputes that occur and then escalate into big problems. This is of course very unfortunate, Indonesian culture has declared democracy but the democracy that has been declared has not run smoothly. Legal protection for victims of mob violence is through compensation which is civil in nature, arises from the victim's request and is paid by the community/state or is a form of community and state accountability, restitution is criminal in nature, arises from a criminal court decision and is paid by the convict or the perpetrator of the crime. , or is a form of criminal responsibility and the factors that cause mass riots are socio-cultural factors, economic factors,